2009
DOI: 10.1371/journal.pone.0005003
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the WNK1 Gene Are Associated with Blood Pressure Variation and Urinary Potassium Excretion

Abstract: WNK1 - a serine/threonine kinase involved in electrolyte homeostasis and blood pressure (BP) control - is an excellent candidate gene for essential hypertension (EH). We and others have previously reported association between WNK1 and BP variation. Using tag SNPs (tSNPs) that capture 100% of common WNK1 variation in HapMap, we aimed to replicate our findings with BP and to test for association with phenotypes relating to WNK1 function in the British Genetics of Hypertension (BRIGHT) study case-control resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 47 publications
4
42
0
1
Order By: Relevance
“…The polymorphism rs11571461 was found at a frequency similar to that previously described in Caucasian subjects. 40 However, this polymorphism described downstream of WNK1 is actually located in the RAD52 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphism rs11571461 was found at a frequency similar to that previously described in Caucasian subjects. 40 However, this polymorphism described downstream of WNK1 is actually located in the RAD52 gene.…”
Section: Discussionmentioning
confidence: 99%
“…65,79 Indeed, several population studies now identify single nucleotide polymorphisms and haploptypes in the WNK1 and WNK4 genes that are not only associated with BP variation 80 but also with hypertension severity, 81 salt sensitivity, 82 thiazide sensitivity, 83 and urine potassium excretion. 84 Interestingly, the WNK1 and WNK4 single nucleotide polymorphisms with the strongest associations were either located in or near the sites of the FHHt mutations. 84,85 Although the effects of variants in a single gene may be modest, one study showed that when variants in the genes for WNK1, ␣-adducin (a cytoskeleton protein that also influences Na ϩ -K ϩ -ATPase activity), and Nedd4 -2 (which ubiquinates ENaC) were combined, a significant effect was found on renal salt handling, the BP response to saline and thiazides, and nocturnal systolic BP.…”
Section: Essential Hypertensionmentioning
confidence: 99%
“…There are some data suggesting that rare haplotypes of WNK1 and common variants at the inwardly rectifying potassium channel ROMK may have modest effects on blood pressure. [26][27][28][29][30] In the Framingham Heart Study, the effect of rare variants in the SLC12A3 (NCC), SLC12A1 (NKCC2), and the inwardly rectifying potassium channel, KCNJ1 (ROMK), genes were tested for to see if they influence blood pressure. 31 These genes cause rare recessive disorders with substantial effects on blood pressure (≈6-10 mm Hg systolic).…”
Section: Translation Of Findings From Mendelian Traits Into Populatiomentioning
confidence: 99%